Effect of Force Molting on Postmolt Performance of Laying Hens - Hassanabadi, A.; Kermanshahi, H. (International Journal of Poultry Science, 2007)
An experiment was conducted using 6168 Hyline White hens (79 wk of age) randomly assigned to two dietary treatments. The treatments included high dietary zinc (Zn) and Feed Withdrawal (FW) methods. In the Zn method, hens were fed a layer ration containing 20,000 ppm of zinc as zinc oxide for 10 d and the light was reduced to 12 h/d. At day 11, hens were returned to the control layer ration and received 16 h of light/d. In FW method, feed deprivation was continued for 5 d, water was provided for ad libitum intake and the photo period was reduced to 12 h/d. On day 6, were returned to the control layer ration and received 16 h of light/d. Data were analyzed using student`s T-test procedure of SAS. The hens subjected to Zn and FW methods lost 5 and 20% of their initial body weight by 11 and 6 days of the experiment, respectively. The FW treatment resulted in total cessation of egg production within 7 d and the birds remained out of production until 16 d of the experiment. Hens subjected to Zn treatment ceased egg production by 8 day of the experiment and remained out of production until day 29. The mortality percentage throughout the entire experiment for Zn and FW were 0.057 and 0.032%, respectively which was significantly different. No differences were observed between feed removal treatment and nonfeed removal treatment for postmoult hen day production, egg weight, feed intake, feed efficiency and internal Zn of the eggs laid after Zn treatment. Our results indicated that nonfeed removal method is as effective as feed removal method on postmolt performance, although it caused significantly more mortality.